Pemahaman Relasi Agama, Etika, dan Ekonomi dalam Bingkai Kajian Kontemporer - Rahman, Abdur (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
The relationship between religion, ethics and economics is something that cannot be separated for economic actors, especially Muslims. The aim of all three is to understand three aspects of life in order to obtain blessings between worldly life and the afterlife. In this research research, books and books are used to determine the correlation which is very urgent to discuss considering that the three sentences at first glance are contradictory, one (religion) has the orientation of the afterlife, the other (ethics and economics) has a world orientation, even though implicitly ethics and Economics is an integral part of religion itself.